Mitigation of Flood Stress in Mazamort Pepper Variety through Manganese Application - Sultan Dere; Mehmet Emin Doğan (Turkish Journal of Agriculture: Food Science and Technology)
This study was conducted to investigate the effect of Mn application on the resistance of pepper plants exposed to flood stress. The study was conducted in a climate-controlled room at Siirt University, utilizing the Mazamort three-lobed pepper variety as plant material. In the climate chamber (19 m²), conditions were established at 24±1°C during the day and 18±1°C at night, with a light/dark photoperiod of 16/8 hours. The growing medium consisted of a 2:1 (v) mixture of peat and perlite. Four treatment groups were established: control, flood stress, 2.5 mg/L manganese (Mn), and flood stress combined with 2.5 mg/L Mn. Sixty-day-old Mazamort pepper plants were subjected to continuous flooding and manganese application at each watering. The duration of flood stress was set at 0 days (control) and 10 days. The experiment was designed using a randomized complete block design with three replications, each containing 10 plants. Parameters evaluated at the end of the study included visual assessment, plant height, stem diameter, leaf number, leaf fresh and dry weight, leaf moisture content, root fresh and dry weight, root moisture content, chlorophyll content (SPAD value), ion leakage, relative water content (RWC), and turgor loss. The highest plant height was observed in the 2.5 mg/L manganese treatment (45.82 cm), while the greatest stem diameter was recorded in the control group. The highest leaf number (30.60) and SPAD value (35.34) were also noted in the control group. RWC was highest at 96.90% in the 2.5 mg/L manganese treatment. The maximum turgor loss was 5.606% in the control group, and the highest ion leakage (17.880%) was observed in the 2.5 mg/L manganese treatment. It was concluded that manganese application mitigated the negative effects of flood stress on various parameters; however, it did not fully restore the values to control group levels.